2012
DOI: 10.1007/s11250-012-0156-7
|View full text |Cite
|
Sign up to set email alerts
|

Some descriptive characteristics of a new goat breed called Honamli in Turkey

Abstract: This study has been carried out in the Western Mediterranean Region of Turkey on seven different Honamli goat flocks. The aim of this study was to determine the growth characters, survival rate (till weaning, 105th day), some reproductive characteristics and marketable milk yield. The data were collected from 516 does and 210 kids (125 buckling and 85 doelings). The results indicate that the numbers of multiple birth and litter size were 32.8 % and 1.35 respectively. Survival rates of kids at the 30th, 90th, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…On the other hand, Honamli goats are usually bred in the provinces of Antalya, Burdur, and Konya, which are located near the foothills of the Taurus Mountains in the western part of the Mediterranean region (14,15). The Honamli goat is a combined productive goat raised for meat, milk, and hair (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Honamli goats are usually bred in the provinces of Antalya, Burdur, and Konya, which are located near the foothills of the Taurus Mountains in the western part of the Mediterranean region (14,15). The Honamli goat is a combined productive goat raised for meat, milk, and hair (14).…”
Section: Introductionmentioning
confidence: 99%
“…The Honamli goat is a combined productive goat raised for meat, milk, and hair (14). Although there are limited reproductive studies about Honamli goats, the findings of some studies (15,16) revealed that the Honamli breed was superior to other local goat breeds in terms of various reproductive characteristics. Similarly, the number of reproductive studies on Hair goats is considerably limited (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…A study on Honamli goat reported that HCT values of kids were 26.3 % and goats were 22.1 %. Researchers decelerated that this could be characteristic for this breed however less nutrient supply from roughage could affect hematocrit values (11). In the study HCT levels of S group was degreased (p<0,05) however S + LYC group has no significance when compared with control group.…”
Section: Discussionmentioning
confidence: 86%
“…Thus the literature is very limited on Honamlı goats due to the nomadic life style of Yörüks. In the previous study performed on Honamlı goats, it was reported that in terms of meat production, Honamlı goats had one of the highest potential among the other goat breeds reared in Turkey (Elmaz et al 2012b). Skeletal muscle development is a prominent and complex biochemical process in meat animals, and it directly affects the meat production (Swatland 1994).…”
Section: Introductionmentioning
confidence: 98%